YouTube, Med-Cram, Online Med-Ed, and Traditional Lectures: A Comparative Study of Healthcare Students’ Preferences: YouTube, Med-Cram, Online Med-Ed, and Traditional Lectures - Butt, Ayesha; Ibrahim, Fazeelat; Jamil, Fiza; Mahmud, Tayyaba; Cheema, Kanwal Hassan; Ijaz, Farhat; Aftab, Rana Khurram (Pakistan Journal of Health Sciences, 2025)
The computer technology revolution drove the widespread adoption of online learning resources in higher education, met the preferences of tech-savvy students, and was accelerated by the pandemic. Objective: To evaluate learning style preference among health care students. Methods: This comparative cross-sectional study was conducted between two groups: the first one attended conventional live lectures, and the second one used other online learning resources for undergraduate students at Combined Military Hospital (CMH) Lahore Medical College (LMC) and Institute of Dentistry (IOD) Lahore from May to July 2024. The study involved 296 undergraduate students from various healthcare disciplines. First-year students were excluded from the study. Data collection employed a validated questionnaire assessing dimensions such as social presence, interaction, and satisfaction. Results: The results revealed a strong preference for in-person learning, citing enhanced engagement, interaction, and immediate feedback as key advantages. Despite the convenience and flexibility of online learning, it fell short in replicating the depth of interpersonal communication and satisfaction achieved in traditional settings. Conclusions: It was concluded that a hybrid learning model, combining the strengths of both approaches, could better address diverse student needs. Future research should explore the effectiveness of such models in improving educational outcomes across healthcare fields.